Articular Cartilage Assessment Using Ultrashort Echo Time MRI: A Review - Afsahi, Amir Masoud; Sedaghat, Sam; Moazamian, Dina; Afsahi, Ghazaleh; Athertya, Jiyo S.; Jang, Hyungseok; Ma, Ya-Jun (Frontiers in Endocrinology, 2022)
Articular cartilage is a major component of the human knee joint which may be affected by a variety of degenerative mechanisms associated with joint pathologies and/or the aging process. Unfortunately, conventional magnetic resonance imaging (MRI) is able to detect signal from neither the deep cartilage layer nor the calcified cartilage zone of articular cartilage as a result of these particular tissues’ short transverse relaxation times (T2s). Several ultrashort echo time (UTE) techniques have recently been developed that are capable of detecting significant signal from all regions of the articular cartilage, making more accurate and useful morphological imaging and quantitative cartilage assessment possible. This review article summarizes the current catalog techniques based on UTE MRI that have been utilized for such purposes in the human knee joint, including T1, T2*, T1ρ, magnetization transfer (MT), and inversion recovery (IR). The contrast mechanisms as well as the advantages and disadvantages of each technique are discussed.